The Royal Castle in Warsaw - Fałkowski, Wojciech (Director's Choice, 2022)
This successful series provides directors with the unique opportunity to share highlights from their own collections. Each book takes the reader on a personal tour, exploring the significance of each work and providing invaluable insight into treasures that may otherwise be overlooked.00Professor Wojciech Falkowski was appointed Director of the Royal Castle in Warsaw ? Museum in 2017. He is an author, historian and academic specialising in the Middle Ages and holds a chair at the University of Warsaw. From 1993 to 2001 he served as the Secretary General of the Polish National Commission for UNESCO